2016
DOI: 10.1332/147084414x14024918243748
|View full text |Cite
|
Sign up to set email alerts
|

Participatory policy making under authoritarianism: the pathways of local budgetary reform in the People’s Republic of China

Abstract: Citizen participation in policy making is essential in democracies, but there is much less understanding of the process and substance of it in non-democratic states. Taking local budgetary process as an example, this article compares three pathways of participatory reform undertaken by the communist regime in China, namely the representative pathway, the consultative pathway and the transparency pathway. All three are initiated and administered by the local governments, but differ in a number of crucial aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Many scholars have recently inquired into the use of horizontal accountability and increasing participation channels for ordinary people in policy formation and design as well as in policy implementation and oversight in China, for example (Benton 2016;Chen, Pan, and Xu 2016;He and Warren 2011;Truex 2016Truex , 2017Xiaojun and Ge 2016). He and Warren (2011, 275) observed that these participation channels in China are carefully managed and channeled into the 'governance level' domain of administrative decision-making (as opposed to regime-level).…”
Section: Government Responsiveness: Leveraging Icts In Public Goods Pmentioning
confidence: 99%
“…Many scholars have recently inquired into the use of horizontal accountability and increasing participation channels for ordinary people in policy formation and design as well as in policy implementation and oversight in China, for example (Benton 2016;Chen, Pan, and Xu 2016;He and Warren 2011;Truex 2016Truex , 2017Xiaojun and Ge 2016). He and Warren (2011, 275) observed that these participation channels in China are carefully managed and channeled into the 'governance level' domain of administrative decision-making (as opposed to regime-level).…”
Section: Government Responsiveness: Leveraging Icts In Public Goods Pmentioning
confidence: 99%
“…Previous debate on PB has paid significant attention to the factors that can lead to PB initiation and, above all, to its design and consequences (Abdel-Monem et al, 2016;Brun-Martos and Lapsley, 2017;Ebdon, 2002), elaborating frameworks to analyze the practice's design and key features (Ebdon and Franklin, 2006;Sintomer et al, 2008). Several studies have investigated the participation mechanisms adopted by governments to realize citizen participation (Geurtz and Van de Wijdeven, 2010;Holdo, 2016;Xiaojun and Ge, 2016), the diverse conditions driving the success of PB (Barbera et al, 2016;Kim and Schachter, 2013;Pinnington et al, 2009), the effectiveness of various approaches used to engage citizens (Lim and Oh, 2016) and the role played by different actors (politicians, managers, consultants, etc. ) in producing PB in practice (Aleksandrov et al, 2018).…”
Section: Previous Literature On Pbmentioning
confidence: 99%
“…While the notion of inputprocess-output approach to understanding participatory institutions has its own merits and shortfalls, it is essential to explore who hosts the participatory processes. Existing literature is evidence to show that there are at least three different actors who have been dominating the 'hosting' role of participatory institutions (Sheely, 2015;Sjoberg, Mellon, & Peixoto, 2017;Yan & Xin, 2016). The first is the government and that governments at different levels organise participatory processes for different purposes, sometimes making the participatory institution a multi-level process with the objective to achieve a single aim (Homsy, Liu, & Warner, 2019).…”
Section: Society-driven Participatory Institution: An Analytical Frammentioning
confidence: 99%